Testing the Target Congruence Approach: Do Vulnerability, Gratifiability, and Antagonism Explain Cyberstalking Victimization Among Young Adults? - Fissel, Erica R. (Criminal justice and behavior, 2023)
To extend theoretical understanding of cyberspace victimization beyond lifestyle-routine activity theory, we tested the target congruence approach as a plausible explanation for cyberstalking victimization. Of secondary interest, we assessed whether the relationship between target congruence and cyberstalking victimization differs by pursued–pursuer relationship. Survey data from a sample of 1,500 young adults (18–25 years old) revealed 32% had experienced cyberstalking victimization within the previous year. Logistic regression results moderately support the target congruence approach. Measures capturing target vulnerability (e.g., age, disability), target gratifiability (e.g., gender identity, types of photos posted), and target antagonism (e.g., relationship status, cyberstalking perpetration) significantly predicted cyberstalking victimization. Moreover, it appears that the target congruence elements better explain cyberstalking victimization conducted by someone known to the target (compared with a stranger). Implications for the applicability of the target congruence approach are discussed, along with suggestions for future research.